5 -La source de financement des investissements de la PME: Une étude empirique sur données sénégalaises: 10.4314/ad.v27i1.22152 - Sall, Mahmoudou Bocar (Africa Development, 2002)
Modem theory in business suggests the existence of a hierarchy in financing investment, because of the failure of costs, of agency costs or relationships between firms and creditors. The purpose of this study is an attempt to point out the existence of a hierarchy in financing small and medium size companies in Senegal. We base an approach on individual data from 1992 to 1999. The results of this descriptive analysis of the sample show that auto- financing is not the preferential approach adopted. Senegalese small and medium size companies do, in many cases, invest on the basis of auto- financing or of debts at the same level importance. The bigger the company, the higher the importance of the rate. We present characteristics on the financing companies as well; they indicate the existence of a structure for the specific financing of the small and medium size companies.